(2E)-3-(3,5-Dimethyl-1-phenyl-1H-pyrazol-4-yl)-1-(2,5-dimethyl-3-furanyl)prop-2-en-1-one - Abdullah Mohamed Asiri (Molbank, 2010)
The title compound, (2E)-3-(3,5-dimethyl-1-phenyl-1H-pyrazol-4-yl)-1-(2,5-dimethyl-3-furanyl)prop-2-en-1-one (3) was synthesized in high yield by an aldol condensation between 3-acetyl-2,5-dimethylfuran and 3,5-dimethyl-1-phenylpyrazole-4-carboxaldehyde in ethanolic NaOH at room temperature. Its structure was fully characterized by elemental analysis, IR, 1H NMR, 13C NMR and EI-MS spectral analysis.